Dynamics of Health Capital Formation and its Implications for Community Health Outcomes: An Analysis at the Individual Level of the Poor in Banten Province - Muhammad Angga Anggriawan; Tata Rustandi; Billy Tejaarief (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines the factors influencing health capital formation and its impact on public health outcomes among the poor in Banten Province using the SEM-PLS method. Health capital is shaped by various aspects, including health education and knowledge, access to healthcare services, environmental conditions, genetic and hereditary factors, lifestyle, as well as physical and mental health. The findings indicate that higher education levels enhance individuals' understanding of health, while easier access to healthcare services contributes to improved community health conditions. Additionally, environmental factors and lifestyle play a crucial role in determining an individual's overall health quality. The objective of this study is to identify the key determinants of individual health capital and analyze their implications for public health. These findings highlight the need for policy interventions focused on improving health education and knowledge, as well as expanding equitable access to healthcare services. Continuous education programs and better healthcare facilities, especially for low-income communities, are recommended. However, this study has limitations, including cross-sectional data and potential self-report biases. Therefore, future research should employ longitudinal data and consider additional variables to gain a deeper understanding of the dynamics of health capital and its impact on public health outcomes.